Deletion of large-conductance calcium-activated potassium channels promotes vascular remodelling through the CTRP7-mediated PI3K/Akt signaling pathway - Bi Jing; Duan Yanru; Wang Meili; He Chunyu; Li Xiaoyue; Zhang Xi; Tao Yan; Du Yunhui; Liu Huirong (Acta Biochimica et Biophysica Sinica, 2022)
The large-conductance calcium-activated potassium (BK) channel is a critical regulator and potential therapeutic target of vascular tone and architecture, and abnormal expression or dysfunction of this channel is linked to many vascular diseases. Vascular remodelling is the early pathological basis of severe vascular diseases. Delaying the progression of vascular remodelling can reduce cardiovascular events, but the pathogenesis remains unclear. To clarify the role of BK channels in vascular remodelling, we use rats with BK channel α subunit knockout (BK α ‒/‒). The results show that BK α ‒/‒ rats have smaller inner and outer diameters, thickened aortic walls, increased fibrosis, and disordered elastic fibers of the aortas compared with WT rats. When the expression and function of BK α are inhibited in human umbilical arterial smooth muscle cells (HUASMCs), the expressions of matrix metalloproteinase 2 (MMP2), MMP9, and interleukin-6 are enhanced, while the expressions of smooth muscle cell contractile phenotype proteins are reduced. RNA sequencing, bioinformatics analysis and qPCR verification show that C1q/tumor necrosis factor-related protein 7 ( CTRP7) is the downstream target gene. Furthermore, except for that of MMPs, a similar pattern of IL-6, smooth muscle cell contractile phenotype proteins expression trend is observed after CTRP7 knockdown. Moreover, knockdown of both BK α and CTRP7 in HUASMCs activates PI3K/Akt signaling. Additionally, CTRP7 is expressed in vascular smooth muscle cells (VSMCs), and BK α deficiency activates the PI3K/Akt pathway by reducing CTRP7 level. Therefore, we first show that BK channel deficiency leads to vascular remodelling. The BK channel and CTRP7 may serve as potential targets for the treatment of cardiovascular diseases.